Examining the psychometric properties of the Wong and Law Emotional Intelligences Scale (WLEIS) - Wan Shahrazad Wan Sulaiman,; Mohd Zainuddin Mohd Noor, (Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2015)
Emotional intelligence is an individual’s ability to perceive accurately, evaluate and express emotions. One of the instruments to measure emotional intelligence is the Wong and Law Emotional Intelligence Scale (WLEIS) which consist of four dimensions namely self-emotional appraisal, others’ emotional appraisal, regulation of emotion and use of emotion. The main aim of this research was to evaluate the psychometric properties of the Wong and Law Emotional Intelligence Scale (WLEIS). This was a survey research using a set of questionnaires. A total of 150 newly appointed administrative officers who were undergoing a compulsory course participated in this study. The instruments used were the Wong and Law Emotional Intelligence Scale (WLEIS), Organisational Commitment Questionnaire and the Satisfaction with Life Scale (SWLS). In evaluating the reliability of WLEIS, alpha Cronbach and split half methods were used. In addition, criterion and construct validity methods were used to test its validity. Results obtained showed that the Bahasa Malaysia version of the WLEIS was valid and using principal component analysis with varimax rotation method, four components were extracted with 75.1% variance. The WLEIS also showed good criterion validity from the significant correlations with the criteria of organizational commitment and satisfaction with life. Furthermore, the results of reliability were satisfactory with alpha Cronbach ranging from 0.83 to 0.92 for all the dimensions. Results of split half reliability also showed the instrument was reliable with the coefficient ranging from 0.81 to 0.95.